An Iron IIA Iron and Bronze Workshop in the Lower City of Tell es-Safi/Gath - Workman, Vanessa; Maʾir, Aharon 1958-; Dagan, Amit; Regev, Johanna; Boaretto, Elisabetta; Eliyahu-Behar, Adi (2020)
An iron and bronze workshop in the lower city of Tell es-Safi/Gath, dated to the mid-late Iron IIA, contributes new data on the chronology, organization, and practice of metal production in the urban Philistine setting. Analyses show that iron objects were likely produced and maintained on a large scale, alongside bronze, employing regionally unique forms of crucibles and tuyères. The material culture of metalworking is discussed in relation to contemporaneous iron production sites in the region, building a more robust picture of the adoption of iron metallurgy in the Levant versus the status of bronze and iron.
Keywords: Tell es-Safi/Gath; Iron IIA; Philistia; Metal crafts; Copper/bronze working; Iron production